2015
DOI: 10.26577/2218-7979-2015-8-2-18-22
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of physiologically active polysaccharides from wheat tissue culture

Abstract: Polysaccharides (PS) from wheat cell culture were isolated by liquid-liquid extraction. The molecular mass distribution was determined by gel-permeation chromatography (GPC) using dual detectors for the simultaneous detection. It was supposed that PS sample from wheat cell culture has molecular weight of 1632 Da. The physic-chemical properties of PS such as solubility in different solvents, surface activity, ξ-potential, the pH value, polydispersity (PDI) were determined. The PS sample was soluble in water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our previous research enabled us to identify bioactive polysaccharides in cereal cell suspension cultures [ 30 ]. We explored the chemical composition and physical properties of these wheat PSs, which were found to be represented by arabinogalactans and supposed to be represented by xyloglucans, arabinoxylans, and glucans, according to their monosaccharide composition [ 31 , 32 ]. In addition, we showed that monosaccharide composition changed significantly depending on the cultivation media [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research enabled us to identify bioactive polysaccharides in cereal cell suspension cultures [ 30 ]. We explored the chemical composition and physical properties of these wheat PSs, which were found to be represented by arabinogalactans and supposed to be represented by xyloglucans, arabinoxylans, and glucans, according to their monosaccharide composition [ 31 , 32 ]. In addition, we showed that monosaccharide composition changed significantly depending on the cultivation media [ 33 ].…”
Section: Introductionmentioning
confidence: 99%